ANALISA ARUS KAS DALAM PERBAIKAN MANAJEMEN KAS PADA PT BINA RAHMAD MADANI - MEGA SANJAYA; ESTER MANDROFA (LP2MTBM MAKARIOZ, 2021)
PT Bina Rahmad Madani is a moving company in the field of CPO production and management, where the company is still not maximal in managing its cash flow reporting, so the cash management has not been so maximal in increasing the number of liquidity that the company is targeting, where the cash current report over the 2021 period has experienced greater cash production, when compared to previous years, so it affects the company's cash-strapped ability to be unfavourable, as a result of which it affects the company's ability to produce liquidity to continue its operations. If in the coming year the production of this cash is getting bigger. This study aims to find out how the management of the kas currents of PT Bina Rahmad Madani Medan in 2021 can improve the existing cash management of the company. The data analysis is done using qualitative descriptive data analysis, which is using the cash current growth formula in 2020-2021, where the object of this research is the kas current report PT Bina Rahmad Madani the last 2 years of 2020-2021. TThe results of the research done through the 2020-2021 cash current growth analysis on PT Bina Rahmad Madani can be concluded that this company has not been able to manage well the cash current in the operating and funding section, thus affecting the company's autonomy, due to the limited liquidity of the company to launch the company's operations, so it can be said that the cash management in this company is still not very good..